The John W. Knutson Distinguished Service Award in Dental - Herschel S. Horowitz, DDS, MPH (2000)
As you know, the recipient of the 1999 John W. Knutson Distinguished Service Award, conferred by the Oral Health Section of the American Public Health Association, is Viron Leroy Diefenbach, otherwise known as Dief